The WWOX Gene Influences Cellular Pathways in the Neuronal Differentiation of Human Neural Progenitor Cells - Kośla, Katarzyna; Płuciennik, Elżbieta; Styczeń-Binkowska, Ewa; Nowakowska, Magdalena; Orzechowska, Magdalena; Bednarek, Andrzej K. (Frontiers in Cellular Neuroscience, 2019)
The brain is the most functionally organized structure of all organs. It manages behavior, perception and higher cognitive functions. The WWOX gene is non classical tumor suppressor gene, which has been shown to have an impact on proliferation, apoptosis and migration processes. Moreover, genetic aberrations in WWOX induce severe neuropathological phenotypes in humans and rodents. The aim of the present study was to investigate in detail the impact of WWOX on human neural stem cell maintenance and how depletion of WWOX disturbs signaling pathways playing a pivotal role in neuronal differentiation and CNS organogenesis. Human neural stem cells with a silenced WWOX gene exhibited lowered mitochondrial redox potential, enhanced adhesion to fibronectin and extracellular matrix protein mixture, downregulation of MMP2/9 expression and impaired 3D growth. Global transcriptome analysis using CAGE found that WWOX downregulation significantly changes the expression of multiple genes engaged in cytoskeleton organization, adhesion, cell signaling and chromatin remodeling. The massive changes in gene expression caused by WWOX silencing may strongly affect the differentiation and migration of neurons in organogenesis, brain injury, cancerogenesis or neurodifferentiation. WWOX gene appears to be an important regulator of neural tissue architecture and function.